Legitimising lithium mining: Global energy transition and green developmentalism in Jujuy, Argentina - Felix Malte Dorn; Kristina Dietz (European Review of Latin American and Caribbean Studies)
The global green energy transition towards a low-carbon economy via decarbonisation is in-creasing the demand for and exploitation of so-called critical resources, including lithium. The growing demand for lithium, which, as a raw material, is primarily found in countries of the global South, has sparked a new debate on the global interdependencies, unequal ecological and economic exchange and unevenness of the energy transition between the global North and South. In this context, concepts such as green extractivism, green colonialism and green sacri-fice zones have emerged. In this article, we build on this strand of literature, assuming that decarbonisation – as the overarching goal of the energy transition – influences the decisions taken over lithium mining and the narratives used for its legitimisation. It remains an open question, however, how the legitimisation of lithium mining is being shaped by decarbonisa-tion and energy transition goals. What narratives are being used, by whom, how and with what socio-political and socio-economic effects? In Argentina, there are numerous lithium mining projects, and conflicts only arise in a fraction of them. We focus on two lithium mining projects at the Salar de Olaroz-Cauchari, Jujuy, where protests against the mines have been largely absent. We analyse the narratives applied by governmental and corporate actors. The theoretical underpinning of the analysis is based on a dialectical understanding of narratives, whereby narratives are seen as contingent products of social and global-local (multiscalar) interactions. We argue that, in order to become powerful and to legitimise lithium mining, two core narratives are applied by its proponents: a green development and industrialisation narra-tive and a climate protection narrative. Both narratives are increasingly linked to global dis-courses of green energy transition and are part of an emerging green developmentalist disposi-tive that manifests in new institutions, laws and administrative measures to enforce lithium mining. Resumen: Legitimando la extracción de litio: Transición energética global y desarrollismo verde en Jujuy, Argentina La transición energética ecológica mundial hacia una economía baja en carbono a través de la descarbonización está aumentando la demanda y la explotación de los denominados recursos críticos, entre ellos el litio. La creciente demanda de litio, que, como materia prima, se encuen-tra principalmente en países del Sur global, ha suscitado un nuevo debate sobre las interdepen-dencias globales, el intercambio ecológico y económico desigual y las desigualdades de la transición energética entre el Norte y el Sur globales. En este contexto han surgido conceptos como extractivismo verde, colonialismo verde y zonas de sacrificio verde. En este artículo nos basamos en esta corriente de la literatura, asumiendo que la descarbonización como objetivo global de la transición energética influye en las decisiones que se toman sobre la extracción de litio y en las narrativas que se utilizan para legitimarla en las regiones ricas en litio. Sin embar-go, sigue siendo una incógnita cómo los objetivos de la descarbonización y la transición ener-gética influyen en la legitimación de la minería del litio. ¿Qué narrativas se utilizan, quién las utiliza, cómo y con qué efectos sociopolíticos y socioeconómicos? En Argentina existen nume-rosos proyectos de extracción de litio pero los conflictos sólo surgen en una parte de ellos. Nos centramos en dos proyectos mineros de litio en el Salar de Olaroz-Cauchari, Jujuy, donde las protestas contra las minas han sido prácticamente inexistentes. Analizamos las narrativas aplicadas por los actores gubernamentales y empresariales. El sustento teórico del análisis se basa en una comprensión dialéctica de las narrativas, según la cual las narrativas son vistas como productos continuos de interacciones sociales y globales-locales (multiescalares). Soste-nemos que, para hacerse poderosos y legitimar la minería del litio, sus defensores aplican dos relatos básicos: el del desarrollo y la industrialización ecológicos y el de la protección del cli-ma. Ambas narrativas se vinculan a los discursos globales sobre la transición energética y forman parte de un dispositivo verde desarrollista emergente que se manifiesta en nuevas insti-tuciones, leyes y medidas administrativas para imponer la minería del litio.